👤
Marcela16
a fost răspuns

65 +(45 :9 +81 :a-2×0+3×4)-46 = 45

Răspuns :

65 +(45 :9 +81 :a-2×0+3×4)-46 = 45
65+(5+81:a-0+12)-46=45
65-46+ (
81:a+17) =45
19+(81:a+17)=45
81:a+17 = 45-19
81:a+17 =26
81:a=26-17
81:a = 9
a=81:9
a=9
65 + ( 45 : 9 + 81 : a - 2 × 0 + 3 × 4 ) - 46 = 45
65 + ( 5 + 81 : a - 0 +12 ) - 46 = 45
65 + ( 5 + 81 : a - 0 +12 )= 45 + 46 
65 + ( 5 + 81 : a - 0 +12 ) = 91
5 + 81 : a - 0 +12 = 91 - 65
5 + 81 : a - 0 +12 = 26 
5 + 81 : a - 0 = 26 - 12
5 + 81 : a - 0 = 14
81 : a = 14 + 0 - 5 
81 : a = 9
a = 81 : 9
a = 9